Dexter's Personality Development Reflected In David Nicholls' One Day (2009): A Psychoanalytic Approach - Arizona, Susanti Wita; , Drs. H. Abdillah Nugroho, M.Hum; , Nur Hidayat, S.Pd (2013)
This study is about Personality Development. The problem of this study is to reveal how the personality development in major character during time to time for almost twenty years is reflected in One Day novel created by David Nicholls published in 2009. There are two objectives: the first is to analyze the novel in term of structural elements and the second is to analyze the novel based on Psychoanalytic Approach. The object of the study is One Day novel by David Nicholls. It used Psychoanalytic Approach. This study belongs to qualitative research. In this research, there are two types of data, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in the One Day novel, David Nicholls deliver message that personality development is important in everyone's life because it is absolutely needed. Second, based on the psychoanalytic approach the result shows that the most influential aspect in the personality development is the avidity from ourselves.